Analisis Pemidanaan pada Anak yang Melakukan Tindak Pidana dalam Perspektif KUHP Nasional 2023 - Yolanda Fitria Salma; Ahmad Irzal Fardiansyah; Dona Raisa Monica; Tri Andrisman; Nikmah Rosidah (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
The enactment of Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP Nasional 2023) has brought significant changes to the national penal system, particularly in the regulation of sanctions imposed on children who commit criminal offenses. Children as offenders constitute a special legal subject who require a sentencing approach oriented toward protection, guidance, and rehabilitation. This study aims to analyze the regulation and concept of sentencing for children under the perspective of the KUHP Nasional 2023 and to assess its conformity with the principles of child protection and the objectives of the juvenile justice system in Indonesia. This research employs a juridical descriptive method using statutory and conceptual approaches through a literature review of primary, secondary, and tertiary legal materials. The findings indicate that the KUHP Nasional 2023 normatively accommodates a more humane sentencing approach by emphasizing the objectives of punishment and providing non-custodial sanctions and rehabilitative measures. However, these provisions remain general and have not been explicitly integrated with restorative justice principles as stipulated in the Juvenile Criminal Justice System Act. Therefore, regulatory harmonization and consistent implementation are necessary to ensure that sentencing for children truly reflects the best interests of the child and the rehabilitative goals of the juvenile justice system.